Challenges and opportunities for China entering global research and development for emerging infectious diseases: a case study from Ebola experience - Chao Li; Jing-Yi Chen; Yang-Mu Huang (BMC, 2020)
Abstract Background China has emerged as a powerful platform for global pharmaceutical research and development (R&D) amid the 2014 Ebola outbreak. The research and development impact of developing countries on prevention and control of infectious disease outbreaks has long been underestimated, particularly for emerging economies like China. Here, we studied its research and development progress and government support in response to Ebola outbreak by timeline, input, and output at each research and development stage. This study will contribute to a deeper understanding of the research and development gaps and challenges faced by China, as well as providing evidence-based suggestions on how to accelerate the drug development process to meet urgent needs during future outbreaks. Methods Data were obtained from the National Nature Science Foundation of China database, PubMed database, Patent Search System of the State Intellectual Property Office of China, National Medical Products Administration, national policy reports and literature between Jan 1st, 2006 and Dec 31st, 2017. An overview of research funding, research output, pharmaceutical product patent, and product licensed was described and analyzed by Microsoft Excel. A descriptive analysis with a visualization of plotting charts and graphs was conducted by reporting the mean ± standard deviation. Results China has successfully completed the research and development of the Ebola Ad5-EBOV vaccine within 26 months, while the preparation and implementation of clinical trials took relative long time. The National Nature Science Foundation of China funded CNY 44.05 million (USD 6.27 million) for Ebola-related researches and committed strongly to the phase of basic research (87.8%). A proliferation of literature arose between 2014 and 2015, with a 1.7-fold increase in drug research and a 2.5-fold increase in diagnostic research within 1 year. Three years on from the Ebola outbreak, six Ebola-related products in China were approved by the National Medical Products Administration. Conclusions China has started to emphasize the importance of medical product innovation as one of the solutions for tackling emerging infectious diseases. Continuing research on the development of regulatory and market incentives, as well as a multilateral collaboration mechanism that unifies cross-channel supports, would advance the process for China to enter global R&D market more effectively.